The Role Of Organizational Learning On Employee Performance Employees Of A Water Treatment Plant Company In Tangerang - Voluntas Tua, Caesar Fiat; Negoro, Dimas Angga (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research aims to explore the role of organizational learning on organizational commitment and job satisfaction, both of which impact employee performance. Additionally, other factors such as organizational culture and employee participation also influence job satisfaction in order to enhance employee performance. This study is a development of previous research in the financial sector, hospitals, schools, and civil servants. To collect research data, purposive sampling technique was used to gather online questionnaires involving 202 employees of the Water Treatment Plant in Tangerang. The research results show that organizational learning, along with elements such as organizational culture and employee participation, enhances job satisfaction. Additionally, organizational learning also increases organizational commitment. In the end, these two factors support the improvement of employee performance at the Water Treatment Plant in Tangerang. This implies the importance of the organization in creating an atmosphere that supports the learning process in the workplace to enhance employee commitment and job satisfaction, thereby improving employee performance.